Combining aerobic exercise and repetitive transcranial magnetic stimulation to improve brain function in health and disease. (December 2017) - Hendrikse, Joshua; Kandola, Aaron; Coxon, James; Rogasch, Nigel; Yücel, Murat
Highlights: Diminished and maladaptive neuroplasticity are features of neuropsychiatric diseases. Aerobic exercise (AE) may prime plasticity via neurotrophins and neurogenesis. TMS can modulate synaptic efficacy and increase brain network connectivity. Coupling of TMS and AE may have a synergistic effect on neuroplasticity. This novel non-pharmacological combination may improve treatment efficacy. Abstract: The aetiology of various psychiatric and neurological disorders may be partially attributable to impairments in neuroplasticity. Developing novel methods of stimulating neuroplasticity is a promising treatment approach to counterbalance these maladaptive influences and alleviate symptomologies. Two non-pharmacological approaches with significant and direct impacts on neuroplasticity are aerobic exercise and repetitive transcranial magnetic stimulation. Aerobic exercise is associated with the promotion of numerous neurotrophic mechanisms at a molecular and cellular level, which have a broad influence on neuroplasticity. Transcranial magnetic stimulation is a form of non-invasive brain stimulation with the capacity to modulate the synaptic efficacy and connectivity of particular brain networks. This review synthesises extant literature to explore the complementary physiological mechanisms targeted by aerobic exercise and repetitive transcranial magnetic stimulation, and to substantiate the hypothesis that the use of these techniques in tandem may result in synergistic impact on neural mechanisms to achieve a more efficacious therapeutic approach for mental disorders.